KARNAUGH MAP (S.O.P.)
- Reduce the following Boolean Expression
using K-Map :F(P,
Q, R, S) = Æ© (0, 1, 2, 4, 5, 6,
8, 12)
- Reduce the following Boolean Expression using K-Map
:F (A, B, C, D) = Æ© (0,
1, 2, 4, 5, 6, 8, 10)
- Reduce the following Boolean Expression using K-Map :
F(A, B, C, D) Æ© (2,
3, 4, 5, 6, 7, 8, 10, 11)
- Reduce the following Boolean Expression using K-Map
:
F(P, Q, R, S) = Æ© (1,
2, 3, 4, 5, 6, 7, 8, 10)
- Reduce the following Boolean Expression using K-Map
:
F (P, Q, R, S) = Æ© (0, 1,
2, 3, 5, 7, 8, 9, 10, 14, 15)
- Reduce the following Boolean Expression using K-Map
:
F (U, V, W, Z) = Æ© (1,
4, 5, 9, 11, 12, 13, 15)
- Reduce the following Boolean Expression using K-Map
:
F (A, B, C, D) = Æ© (0,
1, 2, 3, 6, 7, 8, 9, 12, 13, 15)
- Reduce the following Boolean Expression using K-Map
:
F (A, B, C, D) = Æ© (1,
3, 4, 5, 6, 7, 12, 13)
- Reduce the following Boolean Expression using K-Map
:
F (W, X, Y, Z) = Æ© (0,
1, 6, 8, 9, 10, 11, 12, 15)
- Reduce the following Boolean Expression using K-Map
:
F (X, Y, Z, W) = Æ© (0,
1, 4, 5, 6, 7, 8, 9, 11, 15)
- Reduce the following Boolean Expression using K-Map
:
F (A, B, C, D) = Æ© (1,
2, 3, 4, 5, 8, 9, 10, 11, 15)
- Reduce the following Boolean Expression using K-Map
:
F (X, Y, Z, W) = Æ© (2, 6,
7, 8, 9, 10, 11, 13, 14, 15)
- Reduce the following Boolean Expression using K-Map
:
F (U, V, W, Z) = Æ© (0,
2, 5, 7, 8, 10, 13, 15)
- Reduce the following Boolean Expression using K-Map
:
F (X, Y, Z, W) = Æ© (0,
1, 2, 3, 4, 5, 10, 11, 14)
- Reduce the following Boolean Expression using K-Map :
F (U, V, Z, W) = Æ© (2,
3, 6, 8, 9, 10, 11, 12, 13)
No comments
Post your comments